2019
DOI: 10.1111/nmo.13713
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing speed is no adequate predictor of aspiration in Parkinson's disease

Abstract: Background There is still a lack of a clinical test to reliably identify patients with Parkinson's disease (PD) being at risk for aspiration. Methods In this prospective, controlled, cross‐sectional study, we assessed if swallowing speed for water is a useful clinical test to predict aspiration proven by flexible endoscopic evaluation of swallowing (FEES). Due to this, we measured the swallowing speed for 90 mL water in 115 consecutive and unselected PD outpatients of all clinical stages and 32 healthy control… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…This supported the supposition that despite the water screen's low-cost and easy administration, the use of a speedbased water swallow screen may not be effective for identifying PWPD in non-advanced stages who are experiencing dysphagia but have not yet been referred for formal diagnostic assessment. Our findings agree with Pflug et al [19] that swallow speed ability in a water screen test does not accurately reflect dysphagia or aspiration risk. Different methodologies exploring volume may be more sensitive to detecting aspiration risk in PD [10].…”
Section: Water Swallow Screen and Vfss Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This supported the supposition that despite the water screen's low-cost and easy administration, the use of a speedbased water swallow screen may not be effective for identifying PWPD in non-advanced stages who are experiencing dysphagia but have not yet been referred for formal diagnostic assessment. Our findings agree with Pflug et al [19] that swallow speed ability in a water screen test does not accurately reflect dysphagia or aspiration risk. Different methodologies exploring volume may be more sensitive to detecting aspiration risk in PD [10].…”
Section: Water Swallow Screen and Vfss Resultssupporting
confidence: 90%
“…Participants were provided with 3 ounces of room temperature water via cup, as measured by syringe, and were cued to "drink the water as fast and as comfortably as they could on consecutive sips". Previous research has investigated the application of swallowing speed with a water swallow protocol to detect airway invasion [18,19,20], but with inconsistent findings related to the measure of swallow speed during this test. Therefore, while we did not specifically measure swallow speed, the decreased synchrony of the respiratory-swallow pattern in PWPD [18,21] may be used to identify episodes of aspiration causing an active airway response.…”
Section: Methodsmentioning
confidence: 99%
“…Dysphagia is not just a symptom of late stage PD. In a recent study, Pflug et al (60) used fiberoptic endoscopic evaluation of swallowing (FEES) on 119 consecutive PwPD and found that 20% of the patients with a disease duration of <2 years had aspiration and that 12% (7 out of 57 patients) with H&Y 2 suffered from severe aspiration. Thus, there is a need to manage dysphagia and avoid complications as early as possible.…”
Section: Swallowing Symptomsmentioning
confidence: 99%
“…Clinical bedside predictors of aspiration used for stroke, like the “normal” water swallow test ( 64 ), have been shown to be unreliable in PD ( 65 ). The Dutch guidelines estimating the maximum swallowing volume or the maximum swallowing speed ( 66 ) were not a suitable screening instrument to predict aspiration in PD patients ( 60 ). Increased drooling (sialorrhea) was also deemed a sign of penetration or aspiration ( 67 ) until Nienstedt et al ( 62 , 68 ) found that drooling cannot be considered an early sign of dysphagia.…”
Section: Introductionmentioning
confidence: 99%
“…Simple water-swallowing tests, measurements of volume and speed while drinking fluids and swallowing questionnaires are not predictive of aspiration in PD patients. 9,10 Considering the complex pathophysiology behind dysphagia in PD and the increase of impairments with swallowing solid food, 2 dysphagia and aspiration could be noticeable earlier in this patient group when multi-texture screening tools are applied. The Gugging Swallowing Screen (GUSS), 11 a widely used multi-texture tool developed and validated for acute stroke patients, might be applicable.…”
Section: Introductionmentioning
confidence: 99%